Spin resolved electron density study of YTiO3 in its ferromagnetic phase: signature of orbital ordering. (2019) - Voufack, Ariste Bolivard; Kibalin, Iurii; Yan, Zeyin; Claiser, Nicolas; Gueddida, Saber; Gillon, Beatrice
No abstract available